2001
DOI: 10.1093/nar/29.7.1574
|View full text |Cite
|
Sign up to set email alerts
|

Different dynamics in nuclear entry of subunits of the repair/transcription factor TFIIH

Abstract: We report here the different ways in which four subunits of the basal transcription/repair factor TFIIH (XPB, XPD, p62 and p44) and the damage recognition XPC repair protein can enter the nucleus. We examined their nuclear localization by transiently expressing the gene products tagged with the enhanced green fluorescent protein (EGFP) in transfected 3T3 cells. In agreement with the identification of more than one putative nuclear localization signal (NLS) in their protein sequences, XPB, XPC, p62 and p44 chim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
4
15
0
1
Order By: Relevance
“…In mammalian cells, nuclear entry of a fused GFP-XPD protein is independent of fused GFP-XPB protein and XPD nuclear transport is concluded to be different from that of other TFIIH subunits (Santagati et al, 2001). However, our results suggest that in early fly development, XPD must be assembled with other TFIIH subunits to enter the nuclei.…”
Section: Journal Of Cell Science 119 (18)mentioning
confidence: 58%
“…In mammalian cells, nuclear entry of a fused GFP-XPD protein is independent of fused GFP-XPB protein and XPD nuclear transport is concluded to be different from that of other TFIIH subunits (Santagati et al, 2001). However, our results suggest that in early fly development, XPD must be assembled with other TFIIH subunits to enter the nuclei.…”
Section: Journal Of Cell Science 119 (18)mentioning
confidence: 58%
“…NSs is distributed throughout the cell during RVFV infection (52); however, its ability to suppress transcription has been suggested to require nuclear localization and the formation of filamentous structures inside the nucleus (2). The localization of p62 is predominantly nuclear (24,42), and it is thought that, immediately after translation, it is translocated into the nucleus, where it assembles with the other subunits of TFIIH to form the functional holocomplex (43). Le May et al suggested that RVFV NSs sequesters p44 subunits before the assembly of TFIIH but does not interact with p44 when already associated with XPD within TFIIH (27).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our data are consistent with APLF being engaged in basal interactions with Ku, which may both stabilize APLF and contribute to its nuclear retention. There are other reported examples of small molecular weight and NLS-deficient repair proteins that rely primarily on interactions with NLS-containing proteins, which are involved in their respective repair pathway, to bring them into the nucleus, often in a DNA damage-dependent manner (36,37). This may represent a level of spatiotemporal regulation that is more efficient than simple diffusion.…”
Section: Discussionmentioning
confidence: 99%